Dinâmica espaço-temporal em uma guilda de borboletas frugívoras no limite norte da Floresta Atlântica Nordestina - Barbosa, José Elieudo Dias (2009)
The extent of the Brazilian Atlantic rainforest, a global biodiversity hotspot, has been reduced to less than 7% of its original range. Yet, it contains one of the richest butterfly fauna in the world. Butterflies are commonly used as environmental indicators, mostly because of their strict association with host plants, microclimate and resource availability. This research describes diversity, composition and species richness of frugivorous butterflies in a forest fragment in the Brazilian Northeast. It compares communities in different physiognomies and seasons. The climate in the study area is classified as tropical rainy, with two well defined seasons. Butterfly captures were made with 60 Van Someren-Rydon traps, randomly located within six different habitat units (10 traps per unit) that varied from very open (e.g. coconut plantation) to forest interior. Sampling was made between January and December 2008, for five days each month. I captured 12090 individuals from 32 species. The most abundant species were Taygetis laches, Opsiphanes invirae and Hamadryas februa, which accounted for 70% of all captures. Similarity analysis identified two main groups, one of species associated with open or disturbed areas and a second by species associated with shaded areas. There was a strong seasonal component in species composition, with less species and lower abundance in the dry season and more species and higher abundance in the rainy season. K-means analysis indicates that choice of habitat units overestimated faunal perceptions, suggesting less distinct units. The species Taygetis virgilia, Hamadryas chloe, Callicore pygas e Morpho achilles were associated with less disturbed habitats, while Yphthimoides sp, Historis odius, H. acheronta, Hamadryas feronia e Siderone marthesia likey indicate open or disturbed habitats. This research brings important information for conservation of frugivorous butterflies, and will serve as baseline for future projects in environmental monitoring